Significance of Community Based Forestry for Effective Forest Landscape Restoration. - Dahal, Ganga Ram (Journal of Forest and Livelihood, 2025)
Forest Landscape Restoration (FLR) has attracted global attention with the recent declaration of the Decade on Ecosystem Restoration (2021-2030) by the United Nations (UN), the Bonn Challenge 2011, and New York Declaration 2014 with the aim to bring 350 million hectares of deforested and degraded land into restoration by 2030. FLR serves as a key strategy to bring communities together in identifying and implementing practices that balance ecological, social, and economic benefits across landscapes. The findings from various studies revealed that there are multiple factors behind limited success of restoration despite strong commitment from the national governments. Various studies also highlighted the significant role of local communities in forest management, and recognition of land and forest rights on their behalf as vital elements in ensuring effective forest landscape restoration. However, the significance of community contribution mainly through community based forest management (CBFM) and the need for the security of local communities' rights over forest land resources are so far largely ignored. This paper analyses the overall situation of forest landscape restoration taking the context of Asia region as reference cases with quantitative data and establishes the interrelation between success and failure of restoration with the extent of involvement of local communities and devolution of rights. Finally, the paper suggests specific strategic directions to move forward to recognise the significance of CBFM model in forest landscape restoration.